Efficient Online Compression for MEMS based BCG Wearable Sensors on ULP FPGA - Kulau, U. I.F.; Noshy, Abdelrahman; Ahmed, Abdelalim (INERTIAL 2023 - 10th IEEE International Symposium on Inertial Sensors and Systems, Proceedings, 2023)
Compression of Ballistocardiography (BCG) data is of a great importance specially in the context of wearables and ultra-low power (ULP) applications, respectively. This paper presents an efficient and yet simple compression core for BCG data that can be integrated to MEMS sensor or on ULP FPGAs. The proposed compression technique is a modified delta encoding algorithm that can compress data efficiently ranging from lossless to lossy compression, while the design was derived from BCG specific requirements. The technique offers flexibility with respect to compression performance and signal distortion where compression ratio can be traded for lossless compression and vice verse. Evaluations of 4 BCG data sets show an average compression ratio of 3 with adequate PRDN. This compression core is further implemented in VHDL and it utilizes 234 LUTs of FPGA resources supporting online compression.
Created from Fastlane, Scopus look-up
Keywords: BCG; Data compression; FPGA; MEMS; Ultra-low power; Wearable